THE CONCEPT OF REGIONAL INNOVATION PROJECTS MANAGEMENT - R. V. Savchuk (Nauka ta progres transportu, 2009)
In the paper the basic stages of a new conception of management for regional projects based upon the principles of indicative management and the decision-making models. The conception is based on the peculiarities of regional level of project management revealed by the author.